Investigating conflicting online review information:evidence from Amazon.com. (July 2020) - Kordrostami, Elika; Rahmani, Vahid
Abstract: This paper investigates the conflicting online review information in terms of its effect on purchase intention of individuals, and the sales rank of products on Amazon.com . The first study used a within-subject experimental design, while the second study used real-world data on 6816 items in the Shoe category on Amazon.com . Findings show that the effect of both volume and valence is dependent on valence range such that volume had a significant effect on purchase intention only when valence hit the medium range, and showed no effect when valence was low. Furthermore, valence only showed an effect at low and high ratings.